Sosialisasi dan Pendampingan Pengolahan Air Tanah Berbasis Konservasi Daerah Doyo Baru - Ngaderman, Theodora; Rumabar, Anna Maria; Mini, Marthina; Zebua, Mercyana (Peneliti.net, 2023)
The people of Doyo Baru use wells as their daily for clean water, it is known that Doyo Baru is one of the sub districts with great groundwater potential. This program was created with the intent and purpose to provide understanding to the people in the village of Doyo Baru about the importance of protecting the environment and soil drilling techniques and the depth that is permitted to get groundwater in wells The methods or approaches used for each program are as follows; Questionnaires, outreach, tree planting. Conservation map is a map that depicts an area of Doyo Baru village where there is nature and the environment to protect plants and groundwater. Nature conservation will provide benefits for the preservation of plants and can also prevent floods or landslides etc. The community does not yet understand that groundwater systems are sustainable based on conservation. The recharge area needs to be conserved. Recharge areas are areas that provide the main means of filling groundwater, good natural recharge areas are areas where surface water is able to infiltrate into groundwater. The recharge area needs to be maintained or maintained